Application of Taguchi arrays using DOE for optimizing processing and understanding sputtered coated ZnO TFTs - Kumar, Dinesh; Gomes, Tiago [UNESP]; Misra, Neeraj Kumar; Sahu, Anil Kumar; Kettle, J. (Elsevier, 2021)
This study applies the Taguchi orthogonal array (OA) to improve and optimize the performance of ZnO thin-film transistors (TFT). Radiofrequency (RF) sputtering method was used to deposit the active layer of TFTs. The annealing temperature, environmental conditions, sputter rate, and thin-film thickness were the parameters whose impact on output parameters like mobility was analyzed in the process optimization using design of experiment (DOE). The ZnO TFTs show state-of-the-art performance features, including high saturation mobility (0.83c), high Ion/Ioffratio (104). The optimal configuration was found to be high annealing temperature 450 °C under N2atmosphere, low sputter rate. This paper presents a method that can empower the fast optimization of metal oxide TFTs for future developments in the manufacturing process. If a full factorial design had been implemented, 64 tests would have been necessary, however in this work, we have reduced the number of tests to 9 only using Taguchi method.
Keywords: Metal oxide; Mobility; Optimization; Taguchi Orthogonal Array (OA); ZnO TFTs